A green strategy for maintaining intelligent response and improving antioxidant properties of κ-carrageenan-based film via cork bark extractive addition. (April 2021) - Zhang, Cijian; Sun, Guohou; Li, Jian; Wang, Lijuan
Abstract: A multifunctional intelligent film was acquired by casting and drying a mixed solution of κ-carrageenan and hydroxypropyl methylcellulose (HPMC) with Prunus maackii pomace extract (EPM) as the natural pH indicator and cork bark extract (CBE) as the antibacterial agent. The film morphology and structure were evaluated by scanning electron microscopy. With the increasing CBE content from 0% to 1.2%, tensile strength of the films decreased from 10.67 to 9.37 MPa and elongation at break increased from 43.86% to 63.89%. The barrier performance and thermal stability of the films after CBE addition still met the food packaging standards. When more than 0.4% (w/w) CBE was added, the films could effectively shield ultraviolet rays. Besides, CBE addition to the films endowed excellent antioxidant properties and resistance to food-borne pathogens, ensured pH sensitivity, and extended the service life of the intelligent film. The films maintained good responsiveness in monitoring pork freshness, and the chromaticity difference was more obvious. Thus, the present study developed a multi-functional smart film with antioxidant, antibacterial, and pH-indicating functions. Graphical abstract: Image 1 Highlights: An edible film was prepared from к-carrageenan and hydroxypropyl methylcellulose. Prunus maackii pomace extract and cork bark extract (CBE) were incorporated in the film. CBE enhanced flexibility and light resistance of the film. CBE endowed the film antioxidant, antibacterial properties and intelligent response. The film is potential for lard preservation and pork freshness monitoring.